Comparative study of 3 methods of crimping in orthodontic hooks with two different types of applied force (elastomeric chains and tie-backs) – in vitro study. - Salas Orozco, Marco Felipe; Perez Zarate, Ximena; Zavala Alonso, Norma Veronica; Martinez Zumaran, Alan; Rodriguez Gonzalez, Lucia Catalina; Gutierrez Martinez, Martin Ulises; Del Rio, Diana Leyva (Revista Estomatología, 2023)
Introduction: the objective of this study was to compare 3 methods of crimping orthodontic hooks with 2 different types of force using tiebacks or elastomeric chains. Methods: 100 crimped hooks, 100 dotted hooks and 100 hooks with a V stop bending on the archwire, divided into 6 groups were put to detachment test in a universal machine SHIMADZU 5000 applying force by means of tiebacks and elastomeric chains, for the use of the machine an accessory base and arm was designed to keep the test stable and standardized. Data were analyzed using GraphPad Prims 8 for Windows. Significance was predetermined at a =0.05. The Shapiro–Wilk test was used to test the data for normality. The data were not normally distributed and therefore the Kruskal Wallis test was used to determine differences between groups, followed by Dunn’s multiple comparisons test. Results: The maximum forces obtained for the detachment of an orthodontic hook was up to 2.87kg which was recorded by the group of dotted hooks and with force applied with elastomeric chain and the one with the lowest force was 0.87kg with hooks only crimped. The tie backs showed a more controlled force in all groups and the groups with a “V stop” bend also showed the most stable tests and none displacement of the hook but more eviction and break of the hooks. Conclusions: In the study it was determined that the crimping method is not sufficient for the stability of the hook so pointing it or performing a V stop bend on the wire increases its stability before the maximum force of detachment and clinically gives advantages in the dental movement although it increases the consultation or laboratory time for its realization.